Outstanding investment by direct insurance companies (Edition 2017) (OECD Insurance Statistics, 2017)
This dataset includes statistics related to outstanding investment by direct insurance companies, classifies by investment category (real estate,mortgage loans, shares, bonds, loans, other investment), companies nationality, destination(foreign or domestic), ownership, insurance type, insurer type(direct insurer, reinsurer).Data are expressed in different currencies and are available from 1988 onwards